SINERGITAS PENYELENGGARAAN PEMERINTAHAN DESA PASCA PEMBERLAKUAN UU NO. 6 TAHUN 2014 TENTANG DESA - Sutrisno Purwohadi Mulyono (Masalah-Masalah Hukum, 2014)
Autonomy and democracy village framed by Act No. 6 of 2014 has a deep philosophical basis. Perspective village renewal in the new regulation was formed to develop a vision towards village life independent, democratic and prosperous. In fact, the limited ability of village government in carrying out the functions and roles lead to growth and social change is slow. Villagers tend to be passive. This study aims to identify the needs of the village towards the synergy-based administration of village welfare society (VWS). The results of this study recommends the strengthening of administrative capacity and bureaucratic governance at the village level, in order to create, transparency, participation, and accountability towards good village government.